2020
DOI: 10.15587/2706-5448.2020.203738
|View full text |Cite
|
Sign up to set email alerts
|

Marketing research and design of quality function in the production of innovative product of health purpose

Abstract: Об'єктом експерименту були 600 осіб, потенційні споживачі кисломолочних виробів. Із них 210 практично здорові та 390, які мають певні захворювання. Предметом дослідження були їх споживчі переваги відносно появи на ринку інноваційного продукту оздоровчого призначення. Однією із проблем сьогодення є незаповненість ринку продуктами харчування для осіб на спеціальному дієтичному харчуванні. В ході дослідження встановлено, що 20 % із числа опитаних майже щоденно споживають йогурти питні класичні. 15, 13 та 12 % рес… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This is a fairly good result in terms of specialized dietary purpose, but the pronounced taste of bifidoproducts, which according to the tasters reminded of medicines, can affect consumer preferences. In studies [28][29][30], it was determined that a consumer wants to see the usual organoleptic indicators in the products for special purposes. Microscopic analysis revealed that in the sample of experiment No.…”
Section: Tablementioning
confidence: 99%
“…This is a fairly good result in terms of specialized dietary purpose, but the pronounced taste of bifidoproducts, which according to the tasters reminded of medicines, can affect consumer preferences. In studies [28][29][30], it was determined that a consumer wants to see the usual organoleptic indicators in the products for special purposes. Microscopic analysis revealed that in the sample of experiment No.…”
Section: Tablementioning
confidence: 99%